Fine‐tuning somatostatin receptor signalling by agonist‐selective phosphorylation and dephosphorylation: IUPHAR Review 5. (April 2014) - Schulz, Stefan; Lehmann, Andreas; Kliewer, Andrea; Nagel, Falko
<x xml:space="preserve">Abstract</x> The biological actions of somatostatin are mediated by a family of five GPCRs, named sst1 to sst5. Somatostatin receptors exhibit equally high‐binding affinities to their natural ligand somatostatin‐14 and largely overlapping distributions. The overexpression of somatostatin receptors in human tumours is the molecular basis for diagnostic and therapeutic application of the stable somatostatin analogues octreotide, lanreotide and pasireotide. The efficiency of somatostatin receptor signalling is tightly regulated and ultimately limited by the coordinated phosphorylation and dephosphorylation of intracellular carboxyl‐terminal serine and threonine residues. Here, we review and discuss recent progress in the generation and application of phosphosite‐specific antibodies for human sst2 and sst5 receptors. These phosphosite‐specific antibodies are unique tools to monitor the spatial and temporal dynamics of receptors phosphorylation and dephosphorylation. Using a combined approach of phosphosite‐specific antibodies and siRNA knock‐down screening, relevant kinases and phosphatases were identified. Emerging evidence suggests distinct mechanisms of agonist‐selective fine‐tuning for individual somatostatin receptors. The recently uncovered differences in phosphorylation and dephosphorylation of these receptors may hence be of physiological significance in mediating responses to acute, persistent or repeated stimuli in a variety of target tissues.